Abdominal lymphangioleiomyomatosis in a man presenting with gastrointestinal hemorrhage as the first manifestation: a case report - Zi, Ying; Shi, Yuchen; Shi, Rongjie (Frontiers in Medicine, 2024)
Lymphangioleiomyomatosis (LAM) is a rare, low-grade malignant condition that typically affects women of childbearing age and primarily involves the lungs. While cases involving males and affecting the gastrointestinal tract are exceedingly uncommon. This report discusses an unusual case of abdominal LAM in a male patient with gastrointestinal hemorrhage. The patient, a 70-year-old man, had been experiencing recurrent abdominal pain, occasional black stools, dizziness, and fatigue for over a month before being admitted to the hospital. Diagnostic electronic gastroscopy identified ulcers in the gastric and duodenal bulb with hemorrhage. An abdominal CT scan revealed multiple cystic foci in the retroperitoneum and mesentery, but no masses were found. Despite receiving medical treatment, the patient continued to have black stools and eventually underwent laparoscopic distal subtotal gastrectomy. The pathological results of the excised distal gastric specimens showed LAM-like lesions in the submucosal layer of the pylorus, mesentery of the side of the lesser curvature of the stomach, and small intestine, leading to a diagnosis of abdominal LAM. However, even after the surgery, the patient still experienced recurrent black stools and developed new symptoms of chest tightness and shortness of breath. A follow-up chest CT revealed bilateral pleural effusion and multiple lung cysts, indicating a worsening condition. The patient was then prescribed oral Sirolimus, which resulted in an improvement in symptoms, including black stool, chest tightness, and shortness of breath. This case report provides a detailed account of the progression of an unusual gastrointestinal LAM case and suggests that a combination of surgery and Sirolimus may be effective in managing the condition.